A Dynamic Model to Appraise Strategic Land-Use and Transport Policies - Pfaffenbichler, P. C.; Shepherd, S.P. (European Journal of Transport and Infrastructure Research, 2002)
This paper presents a framework for an ex ante appraisal of urban land use and transport strategies. At the core of this framework is a dynamic land use and transport interaction model. Objective functions and an optimisation routine are used to assess the effects of complex strategies formed by policy instrument combinations with different policy levels possible. The main objective of the underlying study is to promote sustainable policies. Therefore the proposed framework considers either explicitly or implicitly all five domains of the STELLA focus group 4 (environment, safety, health, land use and congestion).